Corrosion resistance properties of hybrid organic–inorganic epoxy–amino functionalised polysiloxane based coatings on mild steel in 3·5%NaCl solution. (November 2013) - Suleiman, R.; Mizanurrahman, M.; Alfaifi, N.; El Ali, B.; Akid, R.
Abstract : New hybrid organic–inorganic coatings have been developed by reacting a mixture of 3-glycidoxypropyltrimethoxysilane (GPTMS) and tetraorthosilicate (TEOS) with 2–4% aminoethylaminopropyl-methylsiloxane dimethylsiloxane (APDMS) copolymer as a modifier. The sol–gel polymerisation of the inorganic components was achieved by base catalysation using NaOH. The resultant base coating (CGA) was further modified using two different corrosion inhibitors: Moly-white 101-ED and Hfucophos Zapp yielding coatings (CGA-M) and (CGA-Z) respectively. The corrosion resistant efficiency of these coatings for the protection of mild steel sheets in 3·5%NaCl electrolyte was assessed using AC and DC electrochemical methods, notably, electrochemical impedance spectroscopy (EIS) and DC polarisation scans. Based on the results, the order of corrosion protection of the above coatings was in the order: CGA-M>>CGA-Z>CGA.